Electromagnetic Wave Equations of Dyon in Arbitrary Media - Joshi, I.; Garia, J. S. (Journal of Scientific Research, 2020)
Dyon is a hypothetical particle in high energy physics that carries simultaneously both electric and magnetic charge. A dyon with zero electric charge is referred to a magnetic monopole. The paper, reports a simple reformulation of Maxwell equations for dyon in arbitrary media. The Lorentz, Coulomb gauge conditions and the wave equations of dyon in arbitrary media are derived in a simple and compact manner.